Effect of geomagnetic storms on l-band scintillation over Ilorin, Nigeria. Issue 11 (1st June 2023) - Oladipo, O.A.; Olawepo, A.O.; Adeniyi, J.O.; Adimula, I.A.; Willoughby, A.A.; Doherty, P.H.
Highlights: Storms effects of l -band scintillation at Ilorin were investigated and reported. Variations in Dst and Bz values were used to explain storms effect on scintillation. Reduction in atomic to molecular ratios were observed during two of the storms. Abstract: A study on the effects of geomagnetic storms on l -band scintillation at Ilorin (latitude = 8.48 °N, longitude = 4.67 °E, Geomagnetic Latitude = 1.89 °S) is presented using newly available data. Three storms with minimum Dst < - 100 n T (i.e. the storm of April 24, 2012, the St. Patrick's day storm of March 17, 2015 and the storm of October 13, 2016) were selected for the study based on the availability of data and the season of frequent occurrence of scintillation at Ilorin. The indices used are the ring current index ( Dst ), the auroral electroject activity index (AE), the horizontal component of the Interplanetary Magnetic Field ( IMFB Z ) and the ratio of the atomic to molecular neutral species. Results showed that the main phase of the April 24, 2012 caused little enhancement in scintillation during the pre-midnight period while scintillation was suppressed during the post-midnight period. However, scintillation was inhibited on the night of the main phase of the storm of March 17, 2015 and slightly inhibited on the night of the main phase of the storm of October 13, 2016. During the recovery phase, little enhancement was observed for the storm of October 13, 2016 while scintillation was inhibited for one day for the April, 24 2012 and for two successive days for the storm of March 17, 2015. The most interesting results was that of St. Patrick's day storm of March 17, 2015 in which scintillation was inhibited for three successive days. The Prompt Penetration Electric Field which brings about enhancement of E × B lifting of ionization based on the local time of the minimum Dst is good enough to explain the observation during April 24, 2012 storm. Whereas, northward turning in IMFB Z values and decay in AE values which causes damping of E × B lifting of ionization were used in explaining observations during the storms of March 17, 2015 and October 13, 2016. In addition, significant reduction is seen in the ratio of the atomic to molecular neutral species especially during the storm of March 17, 2015 in which scintillation was inhibited during the main phase and the first two successive days of the recovery phase.